2009
DOI: 10.1073/pnas.0811900106
|View full text |Cite
|
Sign up to set email alerts
|

Light-assisted deep-trapping of holes in conjugated polymers

Abstract: The injection of positive charge carriers (holes) into a single conjugated polymer chain was observed to be light-assisted. This effect may underlie critical, poorly understood organic electronic device phenomena such as the build-up of functional deeply trapped charge layers in polymer light emitting diodes. The charging/ discharging dynamics were investigated indirectly by a variety of single molecule electro-optical spectroscopic techniques, including an ''image-capture'' approach.nanoparticle ͉ single mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
35
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 37 publications
1
35
0
Order By: Relevance
“…It has been suggested that there are at least two main types of trap states in CPs:1 )shallow trap states, [16][17][18] in which the chargec an be highly mobile and can therefore access al arge amount of material, and 2) deep trap states, in which the charge is immobile and confined within as mall region of the material. [16][17][18][19][20] Fortunately,i np rinciple, the photon statistics obtained from as ingle CP chain contain the information required to differentiate between quenching events arising from either shallow or deep traps, as is outlined in the following.Photon statisticsa re typicallyu sed to count the number of independently emitting entities-fluorophores-present within the observation volumeo faconfocal fluorescencem icroscope. [21][22][23][24] Such counting is achieved by exploitingt he fact that as inglef luorophore can only emit one photon,t wo fluorophores up to two photons and so forth per excited state lifetime, that is, the PL lifetime.…”
mentioning
confidence: 99%
“…It has been suggested that there are at least two main types of trap states in CPs:1 )shallow trap states, [16][17][18] in which the chargec an be highly mobile and can therefore access al arge amount of material, and 2) deep trap states, in which the charge is immobile and confined within as mall region of the material. [16][17][18][19][20] Fortunately,i np rinciple, the photon statistics obtained from as ingle CP chain contain the information required to differentiate between quenching events arising from either shallow or deep traps, as is outlined in the following.Photon statisticsa re typicallyu sed to count the number of independently emitting entities-fluorophores-present within the observation volumeo faconfocal fluorescencem icroscope. [21][22][23][24] Such counting is achieved by exploitingt he fact that as inglef luorophore can only emit one photon,t wo fluorophores up to two photons and so forth per excited state lifetime, that is, the PL lifetime.…”
mentioning
confidence: 99%
“…It also allows predictions of the absolute ionization potentials (IP) of both polaronic localized and free delocalized hole state in solids, revealing large errors in semilocal (sl) DFT functionals that to our knowledge have never been discussed in the literature. This successfully treatment of hole localization and delocalization properties will aid the understanding of charge trapping [8,9] and carrier mobility [10] that are important for organic electronics.A key prerequisite to such studies is the correct choice of DFT functionals. Previous theoretical studies reveal an extreme sensitivity of charge localization to theoretical approximations [6,7,[11][12][13][14].…”
mentioning
confidence: 99%
“…The gas phase ionization potentials of small molecules, arguably related to the energies of localized holes in solids, are however accurately predicted by even the semi-local functionals that we have considered. Our study may contribute to the understanding of possible mechanisms of deep-hole trap states [9] commonly observed in organic electronics, and may potentially be applicable to covalently bonded solids [6,7,[11][12][13].…”
mentioning
confidence: 99%
“…The amount of fluorescence quenching observed upon the injection of a single hole polaron into a polymer chain also varied with the molecular weight: 60% quenching for 150 kDa 8 , 40% quenching for 1000 kDa. 4,12 Point-spread function fitting techniques used to track nanometer-scale position changes of fluorophores 13 were combined with an electro-optical technique developed in the Barbara group 14 to produce bias-modulated intensity-centroid spectroscopy (BIC), used to monitor exciton migration in MEH-PPV as holes were reversibly injected into single polymer chains. 8 This study revealed remarkably long-range energy transfer in the chain, but also showed a curious change in direction of the fluorescence centroid shift when more than one hole was injected into the polymer.…”
Section: Introductionmentioning
confidence: 99%